Mini Riset: Analisis BPJS kesehatan penerima bantuan iuran (PBI) dengan jumlah kontributor di Sumatera Utara - Siregar, Oktavia Sukmayati; Dalimunthe, Ulfa Fadilla; Br. Ginting, Sheila Oktaviani; Gurning, Fitriani P. (Program Studi Sarjana Kesehatan Masyarakat Universitas Prima Indonesia, 2023)
The aim of the research is to find out whether PBI BPJS membership is in accordance with the number of contributors in North Sumatra Province in 2021. In 2021, North Sumatra Province has a population of 14,936,148 people, 789,834 headed families, and 1,273 families that are classified as poor. With the largest proportion of poor households, North Sumatra Province is in eighteenth place. There are still low-income people who do not meet the requirements for a Healthy Indonesia Card but whose contributions are borne by the government or are recognized as recipients of contribution assistance, but there are also people who are considered not low-income but who receive contribution assistance from the government. Quantitative study with descriptive methodology is the research technique used. The result was that based on BPS indicators, North Sumatra Province was categorized as number eighteen in poverty at most, this means that there are still many income-earning people living in this region. Lack of access is an obstacle in obtaining health assistance, only urban areas have access to a lot of assistance. For example in Samosir Regency with the most PBI recipients of 73.47% in 2021, and the smallest PBI recipients in the North Labuanbatu Regency area of 19.09% in 2021. Due to difficult road access, North Labuanbatu Regency only received a small amount of PBI assistance. This states that the number of shares is the same as the number of contributions is not proportional. It was suggested to the government that it was necessary to update poverty indicators and it was suggested to the government of Provinsi Sumatera Utara to re-collect data related to the condition of community poverty so that beneficiaries could be right on target.